(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To review the application of stem cell therapies and stem cell-derived products in ophthalmic diseases. Methods: A narrative review was conducted using PubMed and Google Scholar. Clinical studies published between 2020–2025 on the efficacy, safety, and clinical outcomes of stem cell therapies and extracellular vesicle (exosome) products were analyzed. Results: ESC/iPSC-derived RPE transplantation for late-stage dry AMD showed long-term safety and visual improvement. In LSCD, CALEC achieved 77% complete success at 18 months, while allogeneic SLET maintained epithelialization in 71% of cases at 12 months. Intrastromal ADSC injection improved vision and corneal curvature in keratoconus. MSC-derived exosomes and eye drops improved dry eye indices with good safety. In glaucoma, early studies suggested neuroprotective effects on retinal ganglion cells. Conclusions: Current evidence supports the safety and potential efficacy of stem cell-based therapies in ophthalmology. However, larger trials with long-term follow-up are needed to confirm durable benefits.